2012
DOI: 10.1093/scan/nss016
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomical correlates of cognitive insight in schizophrenia

Abstract: Insight has been mostly studied from a clinical perspective. Recently, attention moved to cognitive insight or the ability to monitor and correct one's erroneous convictions. Here, we investigated the neuroanatomical correlates of cognitive insight. We administered the Beck cognitive insight scale to 45 outpatients with a schizophrenia diagnosis and 45 age- and gender-matched healthy control subjects who underwent a MRI investigation, including high-resolution volumetric and diffusion tensor imaging sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
6
39
1
Order By: Relevance
“…This finding accords with neuroimaging data demonstrating a role for the frontal cortex in mentalizing about oneself (Frith and Frith, 2003;Lombardo et al, 2010). A related set of experiments using the Beck Cognitive Insight Scale has also reported that individuals' scores on the Self-Reflectiveness factor, which taps comprehension of one's own reasoning processes, is dependent on structural integrity and functional activation in circumscribed regions of the prefrontal cortex (Orfei et al, 2012;Pu et al, 2013;Buchy et al, in press;Buchy and Lepage, 2015). Interestingly, greater thickness in frontal cortical foci was also observed in the analysis of Decentration and Mastery, and this is in accordance with the notion that shared neural representations including frontal cortical foci underlie mentalizing about self and others (Lombardo et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…This finding accords with neuroimaging data demonstrating a role for the frontal cortex in mentalizing about oneself (Frith and Frith, 2003;Lombardo et al, 2010). A related set of experiments using the Beck Cognitive Insight Scale has also reported that individuals' scores on the Self-Reflectiveness factor, which taps comprehension of one's own reasoning processes, is dependent on structural integrity and functional activation in circumscribed regions of the prefrontal cortex (Orfei et al, 2012;Pu et al, 2013;Buchy et al, in press;Buchy and Lepage, 2015). Interestingly, greater thickness in frontal cortical foci was also observed in the analysis of Decentration and Mastery, and this is in accordance with the notion that shared neural representations including frontal cortical foci underlie mentalizing about self and others (Lombardo et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…The association between higher levels of negative symptoms and poor illness insight was also confirmed in the meta-analysis carried out by Mintz et al (2003). To further support our findings, other studies showed that poor illness insight is associated with cognitive impairment that is strongly related to prefrontal cortex dysfunction (Aleman et al, 2006;Shad et al, 2006;Orfei et al, 2013), a brain region linked to negative symptoms (Pratt et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…In other words, our results suggest that patients' capacity to reflect upon their thinking problems and to recognize the errors and correct them is not associated with their parents' capacity of reflection, and openness to feedback. This finding suggests that abnormal cognitive insight in schizophrenia patients seems better explained by cognitive factors and abnormal brain functioning existing in patients as demonstrated by previous studies (Buchy et al, 2010(Buchy et al, , 2014Orfei et al, 2013;Pu et al, 2013) rather than influenced by familial environment, measured here by daily contact with a parent. In addition, the comparable levels of cognitive insight were demonstrated by patients and their parents in our study.…”
Section: Sumd Parents Bcis Parentssupporting
confidence: 79%